(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article investigates the effect of preliminary moisture conditioning of yarn-containing textile waste on the quality of secondary fibers. Two humidification methods were examined — water treatment and emulsion treatment using a 3% OP-10 surfactant solution. It was found that the optimal moisture content of the processed material (10–11%) increases fiber plasticity and strength while reducing brittleness and the proportion of short fibers. Emulsion treatment ensures more uniform moisture distribution and improved fiber uniformity. Preliminary moistening is recommended as an effective method for improving the quality of secondary fibers during textile waste recycling.